Effectiveness of Kevlar-Polyethylene Composite Material in Increasing Ballistic Protective Resistance against High Caliber Weapons - Syalenda Rensapuan Maylana Fayza; Sovian Aritonang (CV. AFDIFAL MAJU BERKAH, 2026)
Kevlar-Polyethylene (UHMWPE) composite materials have become a focus in the defense industry to improve the durability of ballistic armor, especially against high-caliber weapons. Kevlar is known for its high tensile strength and resistance to penetration and heat, while UHMWPE offers elasticity and effective energy absorption. The combination of these two materials creates a composite that is not only lightweight, but also able to withstand projectile penetration better through energy dispersion and absorption mechanisms. This study aims to evaluate the effectiveness of Kevlar-Polyethylene composites in providing ballistic protection for high-caliber weapons. The results show that the use of this composite significantly improves ballistic protection performance compared to conventional materials, due to its synergistic properties. In addition, this composite shows good resistance to extreme environments, thereby increasing service life and efficiency in defense applications.